36. INITIAL STUDY TO DISTINGUISH LUNG CANCER AND BENIGN LUNG DISEASE USING SHOX2 GENE METHYL MARKER FROM LUNG BIOPSY AND LIQUID BIOPSY SAMPLE (Vietnam Journal of Community Medicine, 2024)
This study explores the potential of SHOX2 DNA methylation as a biomarker to distinguish lung cancer from benign lung diseases. We conducted analyzes on both lung tissue samples and plasma samples from lung cancer patients and the control group. Using Realtime PCR technology with extendable lock probes and TaqMan probes, we aimed to increase the sensitivity and specificity of the method, which is important in handling samples with low tumor DNA concentrations. Results showed significant detection of SHOX2 methylation in lung cancer patients compared with controls, both in tissue and plasma samples, demonstrating the potential of this marker in early and non-invasive diagnosis of cancer. lung cancer. Statistical analysis confirmed significant differences between the two groups, reinforcing the role of SHOX2 as an effective biomarker. Although the results are promising, further research is needed to confirm the broad applicability of the method. Improving the chances of diagnosing and treating lung cancer, the study highlights the importance of developing new biomarkers and precise analysis technology.
Keywords: DNA methylation; SHOX2; Lung cancer; Liquid biopsy; Realtime PCR.